Comparison of Antioxidant and Alpha-Glucosidase Inhibitory Properties of Moringa peregrina and Ferulago carduchorum Leaf Extracts and Microencapsulation of Superior Plant - Shiva Nouri; Maryam Moslehishad; Seyede Marzieh Hosseini; Mina Etemadi (Journal of Food Quality)
Today, medicinal plants have a crucial role in treating diseases such as diabetes and cancer. These plants do not impose any side effects owing to their bioactive compounds in comparison with chemical drugs. Several studies have demonstrated antioxidant capacity and α-glucosidase inhibitory effects of bioactive compounds from medicinal plants. According to previous studies, Moringa peregrina (MP) and Ferulago carduchorum (FC) are two promising plants in terms of antioxidant capacity and α-glucosidase inhibitory effects. This research followed a three-stage study. In the first stage, the antioxidant and α-glucosidase inhibitory properties of MP and FC ethanolic extracts, native to Iran, were compared using spectrophotometric methods. The results showed that the ABTS•+ radical scavenging and α-glucosidase enzyme inhibitory activities of both plants were dependent on extract concentration. MP exhibited lower IC50 values in both tests, 1.01 and 4.96 mg·mL−1, respectively. Accordingly, the extract of MP was selected for further experiments. In the second stage, total phenolic content (TPC) and GC-MS analysis were conducted on MP extract to investigate the reason behind its antioxidant capacity and α-glucosidase inhibitory properties. Results of assessing total phenolic content (TPC) using the Folin-Ciocalteu method revealed a strong positive correlation between TPC with antioxidant activity (r = 0.94, p<0.05). GC-MS was used to identify phytoconstituents of the extract, leading to the determination of 35 components whose major one was vitamin E (10.2%). To ensure its suitability for food fortification, in the third stage, encapsulation of the MP extract was followed. Microencapsulation was performed using three polymer coatings, and the effects of carriers were investigated on moisture content, solubility, bulk density, microencapsulation yield, particle size, antioxidant activity, and TPC. According to the experiments, antioxidant activity and TPC were retained well in all carriers. Moreover, SEM, DSC, and FTIR analyses confirmed that the extract was well-coated and no surface fractures were observed. The results indicated that MP can be a promising plant for food fortification as a natural antioxidant and antidiabetic source.